2009
DOI: 10.1007/s00425-009-1018-z
|View full text |Cite
|
Sign up to set email alerts
|

Floral visitation and reproductive traits of Stamenoid petals, a naturally occurring floral homeotic variant of Capsella bursa-pastoris (Brassicaceae)

Abstract: Homeotic changes played a considerable role during the evolution of flowers, but how floral homeotic mutants initially survive in nature has remained enigmatic. To better understand the evolutionary potential of floral homeotic mutants, we established as a model system Stamenoid petals (Spe), a natural variant of Capsella bursa-pastoris (Brassicaceae). In the flowers of Spe plants, petals are transformed into stamens, whereas all other floral organs are unaffected. In contrast with most other homeotic mutants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Finally, our previous analyses of architectural transitions among the rhizomorphic lycopsids were a major impetus to our development of a modern theory of saltational evolution, defined as “a genetic modification that is expressed as a profound phenotypic change across a single generation and results in a potentially independent evolutionary lineage” (Bateman, 1994; Bateman and DiMichele, 1994, 2002). The idea of a nongradualistic framework for macroevolution has since progressively accumulated adherents (e.g., Rutishauser, 1995; Carrión and Cabezudo, 2003; Vergara‐Silva, 2003; Theißen, 2006, 2009; Ziermann et al, 2009; Zander 2010; Reuveni and Giuliani, 2012; Rosenblum et al, 2012), and we remain committed to its basic principles. In the case of the multiple transitions from dominant lateral branching to exclusive crown‐branching that are the focus of this paper, it is extremely difficult to envisage a mechanism that would allow a transition from one architecture to the other that was gradual.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our previous analyses of architectural transitions among the rhizomorphic lycopsids were a major impetus to our development of a modern theory of saltational evolution, defined as “a genetic modification that is expressed as a profound phenotypic change across a single generation and results in a potentially independent evolutionary lineage” (Bateman, 1994; Bateman and DiMichele, 1994, 2002). The idea of a nongradualistic framework for macroevolution has since progressively accumulated adherents (e.g., Rutishauser, 1995; Carrión and Cabezudo, 2003; Vergara‐Silva, 2003; Theißen, 2006, 2009; Ziermann et al, 2009; Zander 2010; Reuveni and Giuliani, 2012; Rosenblum et al, 2012), and we remain committed to its basic principles. In the case of the multiple transitions from dominant lateral branching to exclusive crown‐branching that are the focus of this paper, it is extremely difficult to envisage a mechanism that would allow a transition from one architecture to the other that was gradual.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of a specific flower morphology of C. bursa-pastoris individuals in the vineyards south of Mainz in southwestern Germany is known for quite some time (Reichert, 1998). At first sight, this natural mutant is predominantly important for studies of plant geneticists (Nutt et al, 2006;Ziermann et al, 2009;Hintz et al, 2006;Hameister et al, 2013). With a more detailed analysis, several traits became apparent, and population studies led to the insight that the wild type of C. bursa-pastoris and its variant C. apetala even form two different ecotypes, sympatrically occurring at one place over many years (Hameister & Neuffer, 2017; Hameister, Neuffer & Bleeker, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recent field surveys in vineyards revealed that the wild type is the predominant taxon with tens of thousands of individuals, and the Spe occurs with a stable frequency of about 10% (Hameister, Neuffer & Bleeker, 2009). Intriguingly, potential pollinators, especially wild bees, and hoverflies, tend to prefer one over the other type, probably due to differing volatile emissions of the two flower types (Ziermann et al, 2009;Hameister & Neuffer, 2017, Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the overall fitness is similar in both types of plants but with compensatory performances in plant architecture and germination. Insect visitation and floral architecture seem to have a low incidence on global fitness, possibly because the species is mainly self-pollinating (Ziermann et al, 2009).…”
Section: Evolutionary Potential Of Flower Terata: Myth or Reality?mentioning
confidence: 99%